Sustainability Practices in Higher Education Stakeholder Engagement in Promoting Campus Sustainability. - Cuyegkeng, M.A.
Universities have a role in changing mindsets toward sustainable development through education, research, and extension work. Despite the ongoing trend in favor of sustainability initiatives, however, they themselves struggle to transform organizational practices in their own contexts, especially when trying to get the administration?s buy-in and establish stakeholder engagement. Ateneo de Manila University in particular used its response to the decrees of General Congregation 35 (Society of Jesus, 2008) of the Society of Jesus to serve as the foundation of its campus sustainability programs, especially with respect to its translation into policies that affect the university?s ecological footprint and stakeholder engagement. These programs have led to the articulation of the university?s sustainability policies, administrative structures that support sustainability, and publication of sustainability reports and, more importantly, promoted changes in institutional and personal lifestyles.
Keywords: Stakeholder engagement; Relationship with creation; Sustainability campus; Organizational learning